2018
DOI: 10.1080/02670836.2018.1458460
|View full text |Cite
|
Sign up to set email alerts
|

Residual stress generation in metal matrix composites after cooling

Abstract: Effects of reinforcements' shapes, sizes and contents on (a) von-Mises stress along horizontal line in MMCs, (b) directions and distributions of principal stresses inside particles, matrix and interface, and (c) distribution of thermal residual stress in MMCs were analysed in this investigation. It was found that the matrix-particle interfaces experience sudden change of von-Mises stress which depends on the reinforcement shape. The smoothest change of stress was occurred in triangle particle reinforced MMCs. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…[82][83][84] Residual stress is also seen as a major reason for inconsistent microstructure in AM parts, [4] a situation that will be of more concern in MMC fabrication due to the reinforcement-matrix material thermal property differences. A report by Wong [85] stated that residual stress in MMC increases with increase in reinforcement content. Residual stress in MMCs is linked to thermal mismatch between the matrix and the reinforcement, [85] and it has been showed that the stress arises due to accumulated heat during high-temperature processing or heat treatment which results in the retained residual stress during cooling.…”
Section: Residual Stressmentioning
confidence: 99%
See 2 more Smart Citations
“…[82][83][84] Residual stress is also seen as a major reason for inconsistent microstructure in AM parts, [4] a situation that will be of more concern in MMC fabrication due to the reinforcement-matrix material thermal property differences. A report by Wong [85] stated that residual stress in MMC increases with increase in reinforcement content. Residual stress in MMCs is linked to thermal mismatch between the matrix and the reinforcement, [85] and it has been showed that the stress arises due to accumulated heat during high-temperature processing or heat treatment which results in the retained residual stress during cooling.…”
Section: Residual Stressmentioning
confidence: 99%
“…A report by Wong [85] stated that residual stress in MMC increases with increase in reinforcement content. Residual stress in MMCs is linked to thermal mismatch between the matrix and the reinforcement, [85] and it has been showed that the stress arises due to accumulated heat during high-temperature processing or heat treatment which results in the retained residual stress during cooling. [86][87][88] A further effect (nanoscale twins) induced by thermal mismatch is linked to the size of the reinforcement particles, and is reported to be more noticeable at high volume fraction of smaller sized reinforcement particles.…”
Section: Residual Stressmentioning
confidence: 99%
See 1 more Smart Citation
“…The composite melt is thereafter cast into molds and allowed to solidify. The process has some shortcomings including the tendency for segregation [ 2 ], formation of intermetallic phases owing to high-temperature reactions [ 3 ], agglomeration as a result of density difference [ 4 ] and inducement of residual stress due to thermal mismatch [ 5 ], amidst others. The defects earlier mentioned could occur owing to high or low stirring temperature, high or low stirring speed, or other likely reasons.…”
Section: Introductionmentioning
confidence: 99%
“…R ecently, most conventional materials are replaced with composites in various applications, due to their high stiffness, high strength, light weight and good creep resistance [1,2] . Aluminium alloy is commonly used in the high volume casting process because it is one of the most economical materials [3] that can be used for automotive, aerospace and defence industries [4] .…”
mentioning
confidence: 99%